1980
DOI: 10.1002/hed.2890020607
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic evaluation of irradiated cartilage grafts on the facial skeleton of sheep

Abstract: Augmentation mentoplasty is a commonly performed procedure for correction of retrognathia and microgenia. Implantable Silastic prostheses have become the mainstay of therapy, but have some disadvantages. One of the most important complications is erosion of the underlying mandible. An attempt was made to produce an experimental animal model to test the efficacy of irradiated costochondral cartilage in this regard. In order to prevent a biological material from eroding the underlying bone, the irradiated sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Inconsistent results have been reported about the effect of radiation on the resorption rate. While a number of studies have reported successful grafts of radiated cartilage with the least resorption [9,10,22,23], there have been studies reporting higher and earlier resorption of the radiated cartilage. Donald [19] reported in a long-term study of up to 72 months that complete resorption of irradiated cartilage was observed in 87.7% of cases versus 43.8% of cases of chemical-stored cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent results have been reported about the effect of radiation on the resorption rate. While a number of studies have reported successful grafts of radiated cartilage with the least resorption [9,10,22,23], there have been studies reporting higher and earlier resorption of the radiated cartilage. Donald [19] reported in a long-term study of up to 72 months that complete resorption of irradiated cartilage was observed in 87.7% of cases versus 43.8% of cases of chemical-stored cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…7,[15][16][17] Donald 18 investigated animal costal cartilage homografts and calculated total resorption levels varying from 40% in sheep cartilage stored in thimerosal to 89% in irradiated dog cartilage. In another study using radiographic analysis, Donald et al 19 found minimal resorption (1 of 20) in irradiated cartilage homografts implanted in the sheep facial skeleton. Babin et al 20 found that fresh cat costal cartilage autografts and homografts underwent minimal resorption, but that both frozen autografts and irradiated homografts resorbed considerably.…”
Section: Commentmentioning
confidence: 96%
“…Various prostheses, such as implantable Silastic prostheses, have become the mainstay of therapy, but they have some disadvantages such as infection and extrusion. One of the most important complications is erosion of the underlying mandible 2‐4 . On the other hand, cover‐up methods such as fat or bioplast injection are used to correct mild micrognathia 5 …”
mentioning
confidence: 99%
“…One of the most important complications is ero-sion of the underlying mandible. [2][3][4] On the other hand, cover-up methods such as fat or bioplast injection are used to correct mild micrognathia. 5 Cartilage grafts have been commonly used in plastic and reconstructive surgery applications for many different goals, such as auricular reconstruction and rhinoplasty.…”
mentioning
confidence: 99%